1995
DOI: 10.1002/hipo.450050503
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal and postrhinal cortices of the rat: A review of the neuroanatomical literature and comparison with findings from the monkey brain

Abstract: KEY WORDS: parahippocampal, entorhinal polysensory cortex, memory, hippocampal formation,This review is prompted by recent findings that the perirhinal and parahippocampal cortices in the monkey brain are important components of the medial temporal lobe memory system. Given the potential importance of the comparable rcgions 1 0 niemory function in rhe rat brain, it is surprising that so little is known about their neuroanatomy. In fact, there are no comprehensive studies of the borders, cytoarchitecture, or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
495
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 504 publications
(541 citation statements)
references
References 69 publications
29
495
1
3
Order By: Relevance
“…There are a number of anatomical differences (Burwell et al, 1995;Burwell and Amaral, 1998a,b;Pitkä nen et al, 2000;Burwell, 2000Burwell, , 2001) and functional differences (Norman and Eacott, 2005) existing between the two areas and it has been suggested that the rat postrhinal cortex is homologous to the monkey parahippocampal cortex (Burwell et al, 1995;Burwell, 2000). Therefore, we follow Burwell's classification (2000) and distinguish between the perirhinal and postrhinal cortices as two distinct anatomical regions in the rat brain.…”
Section: Anatomical Definition Of the Perirhinal Cortexmentioning
confidence: 88%
See 4 more Smart Citations
“…There are a number of anatomical differences (Burwell et al, 1995;Burwell and Amaral, 1998a,b;Pitkä nen et al, 2000;Burwell, 2000Burwell, , 2001) and functional differences (Norman and Eacott, 2005) existing between the two areas and it has been suggested that the rat postrhinal cortex is homologous to the monkey parahippocampal cortex (Burwell et al, 1995;Burwell, 2000). Therefore, we follow Burwell's classification (2000) and distinguish between the perirhinal and postrhinal cortices as two distinct anatomical regions in the rat brain.…”
Section: Anatomical Definition Of the Perirhinal Cortexmentioning
confidence: 88%
“…Area 35 completely lacks layer IV while area 36 does have layer IV but it appears to be less well defined particularly in the medial portions of the cortex compared to other neocortical areas (Burwell et al, 1995). Brodmann's areas 35 and 36 are also cytoarchitectonically different in that layer I of area 35 tends to be thicker than that of area 36, the cells in area 35 are organised radially, the presence of large, heart-shaped pyramidal cells in layer V of area 35 and finally layers II and III are distinctly separated in area 36 and not in area 35 (Krieg, 1946b;Burwell and Amaral, 1998a,b;Burwell, 2001).…”
Section: Anatomical Definition Of the Perirhinal Cortexmentioning
confidence: 96%
See 3 more Smart Citations